A high barrier single PE composite packaging film for wet wipes packaging and its preparation process

By using a high-barrier single PE composite packaging film made of high-speed solvent-free composite process, the barrier performance of the film is enhanced by using modified montmorillonite, the problem of insufficient barrier performance of existing wet wipe packaging materials is solved, and higher barrier performance and easy recycling effect is achieved.

CN119734468AActive Publication Date: 2025-04-01SUZHOU ZIJIN PLASTIC

Patent Information

Application Number
CN202510237639.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-04-01
Estimated Expiration
2045-03-03

AI Technical Summary

Technical Problem

The barrier properties of existing wet wipe packaging materials are insufficient, resulting in insufficient packaging, which affects the shelf life and recycling of wet wipes.

Method used

A high-barrier single PE composite packaging film made of the outer unidirectional stretched polyethylene film MDOPE, the intermediate layer high-barrier polyethylene film and the inner layer unidirectional stretched polyethylene film MDOPE is used to modify montmorillonite with disulfonate or trisulfonate anionic surfactant to prepare organic-inorganic composite barrier materials to improve the barrier performance of the film.

Benefits of technology

It significantly improves the barrier performance of the wet wipe composite packaging film, with water vapor permeability <1.5g/(m2•24h) and oxygen permeability ≤1.0cm3/(m2•24h•0.1MPa), and is convenient for recycling and recycling, in line with the trend of environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119734468A_ABST
    Figure CN119734468A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wet wipes packaging material research and development, and discloses a high-barrier single PE composite packaging film for wet wipes packaging and a preparation process thereof. The high-barrier single PE composite packaging film is prepared by a high-speed solvent-free composite process of an outer uniaxially stretched polyethylene film, an intermediate high-barrier polyethylene film and an inner uniaxially stretched polyethylene film. The preparation method of the high-barrier polyethylene film comprises: synthesizing a sulfonate type anionic surfactant; under acidic conditions, using a sulfonate type anionic surfactant as an intercalating agent, performing organic modification treatment on sodium montmorillonite, and dispersing the organic-inorganic composite barrier material in an ethylene-vinyl alcohol copolymer matrix to prepare an organic-inorganic composite barrier material; using PE resin as a single raw material and the organic-inorganic composite barrier material as a functional modification agent, and adopting a nine-layer co-extrusion blow molding film-forming process to prepare a high-barrier polyethylene film, which has excellent barrier properties and can be used as an intermediate layer material of the wet wipes composite packaging film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wet wipes packaging material research and development, and in particular to a high-barrier single PE composite packaging film for wet wipes packaging and a preparation process thereof. Background Art

[0002] Wet wipes packaging bags are usually made of polyethylene terephthalate PET and polyethylene PE or oriented polypropylene film OPP and polyethylene PE, but different materials are not conducive to recycling.

[0003] MDOPE is a uniaxially stretched PE film with good rigidity, puncture resistance and heat resistance. It is widely used in food packaging, composite films, vertical liquid packaging bags, industrial packaging and multi-layer packaging films. When used in packaging materials, it can achieve single PE packaging and increase its recyclability. The packaging film products have excellent running performance, high-grade appearance texture and good softness. However, the barrier properties of polyethylene are not very satisfactory. It is usually necessary to use multi-layer composites and increase the barrier layer to meet the needs of packaging products. Barrier properties have always been an important indicator of wet wipes packaging materials, because the shelf life of wet wipes products is directly related to the barrier properties of packaging materials.

[0004] Montmorillonite has a unique natural layered nanostructure and has become a commonly used nanomaterial for improving the barrier properties of thin films. Due to the hydrophilicity of the montmorillonite surface, it is not conducive to its dispersion in the organic phase and wetting by the organic phase. In order to overcome this property, the ion exchange and adsorption of montmorillonite can be used to replace the surfactant (i.e., intercalation agent) with the inorganic cations between the montmorillonite layers, change the environment between the montmorillonite layers, change it from hydrophilic to hydrophobic, reduce the surface energy of the montmorillonite, increase the interlayer distance and specific surface area of ​​the modified montmorillonite, and enhance the ability to adsorb organic matter.

[0005] There are three types of surfactants that can be used to prepare organic montmorillonite: cationic, anionic and nonionic. Currently, the preparation of cationic organic montmorillonite is more common. Research has found that the anionic surfactant sodium dodecyl sulfate is used as an organic intercalant in the modification of montmorillonite, and its effect is better than the commonly used cationic surfactant or organic amine treatment effect; and under acidic conditions, natural montmorillonite can absorb strong acid, and the surface of the sheet is sensitive to H + It has strong binding ability and is more conducive to the adsorption of anionic surfactants. Summary of the invention

[0006] The present invention provides a high-barrier single PE composite packaging film for wet wipes packaging, which is prepared by a high-speed solvent-free composite process of an outer layer uniaxially stretched polyethylene film MDOPE, an intermediate layer high-barrier polyethylene film and an inner layer uniaxially stretched polyethylene film MDOPE which are arranged in sequence. The independently developed high-barrier polyethylene film has the technical effect of significantly improving the barrier properties of the wet wipes composite packaging film, and the composite packaging film adopts a single PE material for easy recycling and cyclic utilization, which is in line with the trend of environmental protection.

[0007] A preparation process of a high-barrier single PE composite packaging film for wet wipes packaging, comprising the following steps: Step 1, setting a product structure of a high-barrier single PE composite packaging film for wet wipes packaging, the product structure consisting of an outer layer uniaxially oriented polyethylene film MDOPE, a middle layer high-barrier polyethylene film and an inner layer uniaxially oriented polyethylene film MDOPE; Step 2: prepare a high barrier polyethylene film, the preparation method of which is as follows: Step 1: synthesizing a disulfonate type anionic surfactant or a trisulfonate type anionic surfactant; Step 2: Under acidic conditions, using a disulfonate type anionic surfactant or a trisulfonate type anionic surfactant as an intercalating agent, the sodium-based montmorillonite is subjected to organic modification treatment to prepare anionic organic montmorillonite; Step 3: dispersing anionic organic montmorillonite in an ethylene-vinyl alcohol copolymer matrix to prepare an organic-inorganic composite barrier material; Step 4: Using PE resin as a single raw material and an organic-inorganic composite barrier material as a functional modification agent, designing the film structure of the nine-layer co-extrusion film, the formula and dosage of each film layer, and adopting a nine-layer co-extrusion blow molding film forming process to prepare a high barrier polyethylene film; Step three, compounding the outer layer uniaxially stretched polyethylene film MDOPE, the middle layer high barrier polyethylene film and the inner layer uniaxially stretched polyethylene film MDOPE through a high-speed solvent-free compounding process to prepare a high barrier single PE composite packaging film for wet wipes packaging.

[0008] Preferably, the formulation and dosage of each film layer of the high barrier polyethylene film are as follows: First layer: the formula is 100wt% low-density polyethylene resin LDPE, the amount is 5-15 parts by weight; The second layer: the formula is 100wt% high-density polyethylene resin HDPE, the amount is 10-20 parts by weight; The third layer: the formula is 100wt% low-density polyethylene resin LDPE, the amount is 5-15 parts by weight; The fourth layer: the formula is 100wt% maleic anhydride grafted polyethylene resin PE-g-MAH, the amount is 3-10 parts by weight; The fifth layer: the formula is 85-95wt% low-density polyethylene resin LDPE and 5-15wt% organic-inorganic composite barrier material, the amount is 10-30 parts by weight; The sixth layer: the formula is 100wt% maleic anhydride grafted polyethylene resin PE-g-MAH, the amount is 3-10 parts by weight; The seventh layer: the formula is 100wt% low-density polyethylene resin LDPE, the amount is 5-15 parts by weight; The eighth layer: the formula is 100wt% high-density polyethylene resin HDPE, the amount is 10-20 parts by weight; Ninth layer: The formula is 100wt% low-density polyethylene resin LDPE, and the amount used is 5-15 parts by weight.

[0009] Preferably, the preparation method of the disulfonate type anionic surfactant is: a ring-opening reaction is carried out between 1 molar equivalent of N,N'-dimethyl-1,8-octanediamine and 2.01-2.09 molar equivalents of 1,3-propanesultone, and the reaction is treated with sodium hydroxide to prepare the disulfonate type anionic surfactant.

[0010] Preferably, the preparation method of the trisulfonate type anionic surfactant is: A sulfonic acid secondary amine monomer is generated by a ring-opening reaction of 1 molar equivalent of 1-decylamine and 1.01-1.09 molar equivalent of 1,3-propane sultone; The trisulfonate type anionic surfactant is prepared by a nucleophilic substitution reaction between the chlorine functional group of 1 molar equivalent of cyanuric chloride and the secondary amine functional group of 3.01-3.09 molar equivalents of sulfonic acid secondary amine monomers, and then treated with sodium carbonate.

[0011] Preferably, the step 2: preparing anionic organic montmorillonite under acidic conditions of pH ≤ 3.

[0012] Preferably, the mass ratio of the disulfonate anionic surfactant or trisulfonate anionic surfactant to the sodium-based montmorillonite in the anionic organic montmorillonite is (0.01-0.1):1; Preferably, the flake diameter of the sodium-montmorillonite is 2-5 μm and the thickness is 3-8 nm.

[0013] Preferably, the mass ratio of anionic organic montmorillonite to ethylene-vinyl alcohol copolymer in the organic-inorganic composite barrier material is (0.05-0.5):1.

[0014] The high barrier single PE composite packaging film for wet wipes packaging prepared according to the above process consists of a uniaxially stretched polyethylene film MDOPE layer with a thickness of 15-25 μm, a high barrier polyethylene film layer with a thickness of 40-60 μm and a uniaxially stretched polyethylene film MDOPE layer with a thickness of 15-25 μm.

[0015] Beneficial effects: The present invention independently developed and synthesized disulfonate type anionic surfactant and trisulfonate type anionic surfactant; Under acidic conditions, sodium-based montmorillonite is organically modified by using a disulfonate anionic surfactant or a trisulfonate anionic surfactant as an intercalating agent to obtain anionic organic montmorillonite; Dispersing anionic organic montmorillonite in an ethylene-vinyl alcohol copolymer matrix to prepare an organic-inorganic composite barrier material; The single recyclable PE material was modified by using an organic-inorganic composite barrier material, and a high barrier polyethylene film was prepared by a nine-layer co-extrusion blow molding process, with a water vapor transmission rate of <1.5g / (m 2 •24h), oxygen permeability ≤1.0cm 3 / (m 2 •24h•0.1MPa), tensile strength>34MPa, that is, the present invention provides a high barrier polyethylene film with very excellent barrier properties, which can be used as the middle layer material of wet wipes composite packaging film. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 These are the performance test results of high barrier polyethylene film. DETAILED DESCRIPTION

[0017] The present invention uses montmorillonite nanosheets and ethylene-vinyl alcohol copolymer with excellent barrier properties as barrier modification raw materials for single PE materials; The hydrophilic and oleophobic properties of inorganic montmorillonite are not conducive to its uniform dispersion in organic ethylene-vinyl alcohol copolymers. Therefore, in order to improve the compatibility of montmorillonite nanosheets and ethylene-vinyl alcohol copolymers, the present invention independently developed a sulfonate-type anionic surfactant. The montmorillonite nanosheets were first organically modified using the new surfactant, and then compounded with ethylene-vinyl alcohol copolymers to obtain an organic-inorganic composite barrier material. Experimental Example 1

[0018] Preparation of disulfonate anionic surfactant: 1 molar equivalent of N,N'-dimethyl-1,8-octanediamine and 2.05 molar equivalents of 1,3-propanesultone undergo a ring-opening reaction, followed by a neutralization reaction under the action of sodium hydroxide to generate a disulfonate anionic surfactant, the chemical structure of which is: ; The specific experimental steps for preparing the disulfonate type anionic surfactant are as follows: 2.5 g of 1,3-propane sultone and 30 mL of ethyl acetate are added to a three-necked flask, stirred at room temperature until completely dissolved, then 20 mL of ethyl acetate solution containing 1.7 g of N,N'-dimethyl-1,8-octanediamine is added dropwise to the three-necked flask, stirred and mixed at room temperature for 30 min, heated to 65°C and stirred for reaction for 40 h, cooled to room temperature, added with 10 mL of a deionized water solution containing 0.5 g of sodium hydroxide, heated to 60°C and stirred for reaction for 5 h, filtered, and the solvent was removed by rotary evaporation, and recrystallized using a mixed solvent of methanol / acetone (the volume ratio of methanol to acetone is 3:2), and vacuum dried to obtain a disulfonate type anionic surfactant; The results of nuclear magnetic resonance hydrogen spectrum characterization of disulfonate type anionic surfactant are as follows: 1 H NMR (CDCl3, 400MHz) δ: 1.31-1.40 (m, 8H), 1.55-1.62 (m, 4H), 1.75-1.82 (m, 4H), 2.23 (s, 6H), 2.29-2.32 (t, 4H), 2.52-2.55 (t, 4H), 2.81-2.85 (t, 4H). Experimental Example 2

[0019] The trisulfonate type anionic surfactant is prepared, and the preparation steps are as follows: Step 1: A sulfonic acid secondary amine monomer is generated by a ring-opening reaction of 1 molar equivalent of 1-decylamine and 1.04 molar equivalent of 1,3-propane sultone, and the chemical structure thereof is: ; Step 2: A nucleophilic substitution reaction is carried out between the chlorine functional group of 1 molar equivalent of cyanuric chloride and the secondary amine functional group of 3.02 molar equivalents of sulfonic acid secondary amine monomers, and a neutralization reaction is carried out under the action of sodium carbonate to generate a trisulfonate type anionic surfactant, whose chemical structure is: ; The specific experimental steps for preparing trisulfonate type anionic surfactant are as follows: 2.5 g of 1,3-propane sultone and 20 mL of ethanol were added to a three-necked flask, stirred at room temperature until completely dissolved, then 30 mL of an ethanol solution containing 3.1 g of 1-decylamine was added dropwise to the three-necked flask, stirred and mixed at room temperature for 30 min, heated to 65° C. and stirred for reaction for 30 h, cooled to room temperature, and the solvent was removed by rotary evaporation, washed with ether, and recrystallized with a mixed solvent of methanol / acetone (the volume ratio of methanol to acetone was 3:2), and vacuum dried to obtain a sulfonic acid secondary amine monomer; 0.9 g of cyanuric chloride, 4.2 g of sulfonic acid secondary amine monomer, 1.7 g of sodium carbonate and 60 mL of methanol were added to a three-necked flask, stirred at room temperature until all dissolved, heated to 70°C, stirred and refluxed for reaction for 12 h, cooled to room temperature, and rotary evaporated to remove the solvent. The mixture was recrystallized using a mixed solvent of ethanol / acetone (the volume ratio of ethanol to acetone was 2:1), and vacuum dried to obtain a trisulfonate type anionic surfactant; The results of nuclear magnetic resonance hydrogen spectrum characterization of trisulfonate type anionic surfactant are as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.89-0.92(t, 9H), 1.21-1.31(m, 36H), 1.35-1.42(m, 6H), 1.64-1.71(m, 6H) ), 2.05-2.12(m, 6H), 2.83-2.86(t, 6H), 3.48-3.51(t, 6H), 3.59-3.62(t, 6H). Experimental Example 3

[0020] Anionic organic montmorillonite I is prepared. The preparation method is as follows: under acidic conditions, sodium montmorillonite is organically modified by using a disulfonate anionic surfactant as an intercalating agent to prepare anionic organic montmorillonite I. The specific experimental steps are as follows: 5g of sodium montmorillonite (purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with specifications of 2-5μm flake diameter and 3-8nm thickness) is added to 200mL of deionized water, ultrasonically dispersed for 30min, 0.1mol / L hydrochloric acid is used to adjust the solution pH to 1, stirred and dispersed at room temperature for 3h, 0.3g of a disulfonate anionic surfactant is added, the temperature is raised to 60°C and stirred for reaction for 5h, cooled to room temperature, centrifuged, washed with ethanol and deionized water in turn, vacuum dried, and ground to obtain anionic organic montmorillonite I; Anionic organic montmorillonite II is prepared by using a trisulfonate anionic surfactant as an intercalating agent to organically modify sodium montmorillonite under acidic conditions to obtain anionic organic montmorillonite II, wherein the specific experimental steps are different from those of anionic organic montmorillonite I only in that a trisulfonate anionic surfactant is used to replace a disulfonate anionic surfactant; Among them, the pH value of the reaction system under acidic conditions is ≤3, and the pH value of the reaction system is selected as 1 in this experimental example. Experimental Example 4

[0021] An organic-inorganic composite barrier material I is prepared, and the preparation method thereof is as follows: anionic organic montmorillonite I is dispersed in an ethylene-vinyl alcohol copolymer matrix to prepare an organic-inorganic composite barrier material I, and the specific experimental steps are as follows: 10g of ethylene-vinyl alcohol copolymer (purchased from Guangzhou Best New Material Technology Co., Ltd., with a brand of ET3803RB) and 1g of anionic organic montmorillonite I are added into a high-speed mixer and mixed evenly, and extruded and granulated by a twin-screw extruder to obtain an organic-inorganic composite barrier material I; The process parameters of the twin-screw extruder were set as follows: the temperatures of zones 1-6 were 160°C, 170°C, 175°C, 180°C, 190°C, and 195°C, respectively, and the rotation speed was 300 r / min; An organic-inorganic composite barrier material II is prepared by dispersing anionic organic montmorillonite II in an ethylene-vinyl alcohol copolymer matrix to obtain an organic-inorganic composite barrier material II. The specific experimental steps are different from those of the organic-inorganic composite barrier material I only in that anionic organic montmorillonite II is used to replace anionic organic montmorillonite I. Embodiment 1:

[0022] A high-barrier single PE composite packaging film for wet wipes packaging, the product structure of which is the following layers arranged in sequence: a uniaxially oriented polyethylene film MDOPE layer, a high-barrier polyethylene film layer, and a uniaxially oriented polyethylene film MDOPE layer; The high-barrier single PE composite packaging film for wet wipes packaging is prepared by compounding a uniaxially oriented polyethylene film MDOPE layer with a thickness of 20 μm, a high-barrier polyethylene film layer with a thickness of 50 μm, and a uniaxially oriented polyethylene film MDOPE layer with a thickness of 20 μm through a high-speed solvent-free compounding process; Among them, the uniaxially stretched polyethylene film MDOPE used in the uniaxially stretched polyethylene film MDOPE layer was purchased from Guangdong Cailong New Materials Co., Ltd.; the high barrier polyethylene film used in the high barrier polyethylene film layer is co-extruded by a first layer, a second layer, a third layer, a fourth layer, a fifth layer, a sixth layer, a seventh layer, an eighth layer and a ninth layer which are arranged in sequence. Embodiment 2:

[0023] Preparation of high barrier polyethylene film: Design the film structure of the high barrier polyethylene film, the formula and dosage of each film layer (the specific contents are shown in Table 1 below), use a nine-layer co-extrusion film blowing unit, and control the blowing ratio at 2.6 to prepare a high barrier polyethylene film with a thickness of 50 μm; Table 1 Experimental formula and process parameters of high barrier polyethylene film

[0024] When the organic-inorganic composite barrier material uses organic-inorganic composite barrier material Ⅰ and Ⅱ respectively, high barrier polyethylene films Ⅰ and Ⅱ are prepared in turn; When the organic-inorganic blended barrier material MMT / EVOH is used to replace the organic-inorganic composite barrier material, a polyethylene film a is prepared, which is used as comparative example 1; Among them, the preparation method of the organic-inorganic blended barrier material MMT / EVOH is: directly mixing sodium-montmorillonite with an ethylene-vinyl alcohol copolymer matrix to prepare the organic-inorganic blended barrier material MMT / EVOH. The specific experimental steps are different from those of the organic-inorganic composite barrier material I only in that the anionic organic montmorillonite I is replaced by sodium-montmorillonite. When ethylene-vinyl alcohol copolymer is used to replace the organic-inorganic composite barrier material, a polyethylene film b is prepared, which is used as comparative example 2; When no organic-inorganic composite barrier material is used (ie, the raw material formula of the fifth layer is 100 wt % of low-density polyethylene resin LDPE), a polyethylene film c is prepared, which is used as Comparative Example 3. Performance Test:

[0025] 1. Barrier performance test: (1) Use TC-03 water vapor transmission tester to test the water barrier properties of the sample in accordance with GB / T 1037-2021 and record the water vapor transmission rate of the sample; (2) Use the Y110 oxygen permeability tester to test the oxygen barrier properties of the sample in accordance with GB / T 1038-2022 and record the oxygen permeability of the sample; 2. Mechanical properties: The mechanical properties of the samples were tested using an Instron 5565 universal tensile testing machine in accordance with GB / T 1040.1-2018. The longitudinal tensile strength of the samples was recorded. The sample size was 150 mm × 20 mm (sampling was performed along the film blowing direction) and the tensile rate was 5 mm / min. The above experimental results are shown in Table 2 and Figure 1 .

[0026] Table 2 Performance test results of high barrier polyethylene film in high barrier single PE composite packaging film for wet wipes packaging

[0027] By comprehensively analyzing the above experimental results, the following conclusions can be drawn: The single recyclable PE material is modified by using organic-inorganic composite barrier materials I and II, and the high barrier polyethylene film obtained thereby has achieved beneficial technical effects of significantly improving both barrier properties and mechanical properties compared to the existing technology; Among them, the organic-inorganic composite barrier material II obtained by compounding montmorillonite modified with trisulfonate type anionic surfactant and ethylene vinyl alcohol copolymer has better dispersibility, swelling and thixotropy, so its modification effect on polyethylene resin will be more significant, and the experimental results have fully confirmed this conclusion.

Claims

1. A preparation process of a high-barrier single PE composite packaging film for wet wipes packaging, characterized in that: The following steps are involved: Step 1, setting a product structure of a high-barrier single PE composite packaging film for wet wipes packaging, the product structure consisting of an outer layer uniaxially oriented polyethylene film MDOPE, a middle layer high-barrier polyethylene film and an inner layer uniaxially oriented polyethylene film MDOPE; Step 2: prepare a high barrier polyethylene film, the preparation method of which is as follows: Step 1: synthesizing a disulfonate type anionic surfactant or a trisulfonate type anionic surfactant; Step 2: Under acidic conditions, using a disulfonate type anionic surfactant or a trisulfonate type anionic surfactant as an intercalating agent, the sodium-based montmorillonite is subjected to organic modification treatment to prepare anionic organic montmorillonite; Step 3: dispersing anionic organic montmorillonite in an ethylene-vinyl alcohol copolymer matrix to prepare an organic-inorganic composite barrier material; Step 4: Using PE resin as a single raw material and an organic-inorganic composite barrier material as a functional modification agent, designing the film structure of the nine-layer co-extrusion film, the formula and dosage of each film layer, and adopting a nine-layer co-extrusion blow molding film forming process to prepare a high barrier polyethylene film; Step three, compounding the outer layer uniaxially stretched polyethylene film MDOPE, the middle layer high barrier polyethylene film and the inner layer uniaxially stretched polyethylene film MDOPE through a high-speed solvent-free compounding process to prepare a high barrier single PE composite packaging film for wet wipes packaging.

2. The preparation process of a high barrier single PE composite packaging film for wet wipes packaging according to claim 1, characterized in that: The formula and dosage of each film layer of the high barrier polyethylene film are as follows: First layer: the formula is 100wt% low-density polyethylene resin LDPE, the amount is 5-15 parts by weight; The second layer: the formula is 100wt% high-density polyethylene resin HDPE, the amount is 10-20 parts by weight; The third layer: the formula is 100wt% low-density polyethylene resin LDPE, the amount is 5-15 parts by weight; The fourth layer: the formula is 100wt% maleic anhydride grafted polyethylene resin PE-g-MAH, the amount is 3-10 parts by weight; The fifth layer: the formula is 85-95wt% low-density polyethylene resin LDPE and 5-15wt% organic-inorganic composite barrier material, the amount is 10-30 parts by weight; The sixth layer: the formula is 100wt% maleic anhydride grafted polyethylene resin PE-g-MAH, the amount is 3-10 parts by weight; The seventh layer: the formula is 100wt% low-density polyethylene resin LDPE, the amount is 5-15 parts by weight; The eighth layer: the formula is 100wt% high-density polyethylene resin HDPE, the amount is 10-20 parts by weight; Ninth layer: The formula is 100wt% low-density polyethylene resin LDPE, and the amount used is 5-15 parts by weight.

3. The preparation process of a high barrier single PE composite packaging film for wet wipes packaging according to claim 1, characterized in that: The chemical structural formula of the disulfonate type anionic surfactant is: 。 4. The preparation process of a high barrier single PE composite packaging film for wet wipes packaging according to claim 3, characterized in that: The preparation method of the disulfonate type anionic surfactant is as follows: 1 molar equivalent of N,N'-dimethyl-1,8-octanediamine and 2.01-2.09 molar equivalents of 1,3-propane sultone undergo a ring-opening reaction, and the reaction is treated with sodium hydroxide to prepare the disulfonate type anionic surfactant.

5. The preparation process of a high barrier single PE composite packaging film for wet wipes packaging according to claim 1, characterized in that: The chemical structural formula of the trisulfonate type anionic surfactant is: 。 6. The process for preparing a high barrier single PE composite packaging film for wet wipes packaging according to claim 5, characterized in that: The preparation method of the trisulfonate type anionic surfactant is as follows: A sulfonic acid secondary amine monomer is generated by a ring-opening reaction of 1 molar equivalent of 1-decylamine and 1.01-1.09 molar equivalent of 1,3-propane sultone; The trisulfonate type anionic surfactant is prepared by a nucleophilic substitution reaction between the chlorine functional group of 1 molar equivalent of cyanuric chloride and the secondary amine functional group of 3.01-3.09 molar equivalents of sulfonic acid secondary amine monomers, and then treated with sodium carbonate.

7. The process for preparing a high barrier single PE composite packaging film for wet wipes packaging according to claim 1, characterized in that: The step 2: preparing anionic organic montmorillonite under acidic conditions of pH ≤ 3.

8. The process for preparing a high barrier single PE composite packaging film for wet wipes packaging according to claim 1, characterized in that: The mass ratio of the disulfonate anionic surfactant or trisulfonate anionic surfactant to the sodium-based montmorillonite in the anionic organic montmorillonite is (0.01-0.1):1; The sodium montmorillonite has a sheet diameter of 2-5 μm and a thickness of 3-8 nm.

9. The process for preparing a high barrier single PE composite packaging film for wet wipes packaging according to claim 1, characterized in that: The mass ratio of anionic organic montmorillonite to ethylene-vinyl alcohol copolymer in the organic-inorganic composite barrier material is (0.05-0.5):

1.

10. A high barrier single PE composite packaging film for wet wipes packaging prepared by the process according to any one of claims 1 to 9, characterized in that: The high barrier single PE composite packaging film consists of a uniaxially stretched polyethylene film MDOPE layer with a thickness of 15-25 μm, a high barrier polyethylene film layer with a thickness of 40-60 μm and a uniaxially stretched polyethylene film MDOPE layer with a thickness of 15-25 μm.

Citation Information

Patent Citations

  • Method for preparing organophilic bentonite

    CN101182393A

  • Preparation method of high polymer blended fat high-resistance membrane

    CN106118041A

  • Coating type multi-layer composite high-barrier film as well as preparation method and application thereof

    CN111703165A

  • Multilayer recoverable ultrahigh-barrier composite film and preparation process thereof

    CN118683146A

  • High-barrier packaging material

    US20070110932A1

Cited By

  • Once-formed all-plastic hose sheet and composite hose thereof

    CN120773424A

  • A one-piece molded all-plastic flexible hose sheet and its composite hose

    CN120773424B